1990
DOI: 10.1002/path.1711620207
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of type I collagen in human kidney diseases in comparison with type III collagen

Abstract: The distribution of type I collagen in normal and diseased renal tissues was studied using immunofluorescence and immunoelectron microscopy, and was compared with that of type III collagen. In normal human kidneys, a monoclonal antibody against type I or type III collagen reacted with the renal interstitium, but not with the intra-glomerular structures. In various types of glomerulonephritis, immunofluorescent staining for type I collagen was positive in the fibrocellular and fibrous crescents, sclerosed glome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
52
0
4

Year Published

1992
1992
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 19 publications
2
52
0
4
Order By: Relevance
“…Because collagen I is a major component in the development of vascular fibrosis, 8 we examined the ability of renal vessels to produce collagen I during chronic NO synthase inhibition. Synthesis of PICP was higher in renal resistance vessels of L-NAME-treated rats than in control rats (4.24Ϯ0.27 versus 2.38Ϯ0.17 ng/mg, nϭ7, PϽ0.05; Figure 6).…”
Section: Collagen I Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because collagen I is a major component in the development of vascular fibrosis, 8 we examined the ability of renal vessels to produce collagen I during chronic NO synthase inhibition. Synthesis of PICP was higher in renal resistance vessels of L-NAME-treated rats than in control rats (4.24Ϯ0.27 versus 2.38Ϯ0.17 ng/mg, nϭ7, PϽ0.05; Figure 6).…”
Section: Collagen I Productionmentioning
confidence: 99%
“…7 Because collagen I is almost absent in renal vessels and glomeruli, it is considered to be a marker of pathophysiological process in abnormal vascular remodeling. 8 Therefore, we hypothesized that longterm blockade of vascular NO production would be associated with enhanced renal vascular production of both ET-1 and collagen I. To this end, we measured ET-1 and collagen I mRNA expression and synthesis.…”
mentioning
confidence: 99%
“…1 This pathophysiological process is associated with changes in the structure of renal vasculature caused by abnormal accumulation of extracellular matrix (mainly collagen type I) in renal resistance vessels, glomeruli, and interstitium. 2 Several recent studies indicated that endothelial vasoactive agents such as nitric oxide (NO) and endothelin could be involved in the development of renal fibrosis. NO is an important inhibitor of vascular smooth muscle cell growth and extracellular matrix synthesis in vitro and in vivo, 3,4 whereas chronic inhibition of NO synthesis is accompanied by renal vascular fibrosis.…”
mentioning
confidence: 99%
“…Hypertension is usually associated with the development of vascular and renal fibrosis [3]. This pathophysiological process is characterized by structural changes in vasculature caused by increased synthesis and rearrangement of extracellular matrix proteins, such as the collagen type I [4]. Several studies support a major role for the renin-angiotensin system in the development of fibrosis [5,6].…”
Section: Introductionmentioning
confidence: 99%